Positive Analysis of Consumer Engagement Towards Brand Trust And Buying Interest On BULOG Rice In Surabaya City - Yusuf, Muhammad; Gunawan, Sri (Universitas Syiah Kuala, 2024)
Rice is a staple food in Indonesia. BULOG Indonesia is a logistics company that produces rice. This study aims to analyze the effect of positive consumer engagement on brand trust, buying interest, and the impact of brand trust on buying interest in BULOG rice in Surabaya. This study uses a quantitative method, processing the data using SmartPLS software. The results of this study are as follows: The explanation is proven by the R-Square value of 0.550 or 55%, meaning that changes in the positive consumer engagement variable can affect the brand trust variable by up to 55%. Therefore, it can be concluded that positive consumer engagement has a positive and significant effect on brand trust in BULOG rice in Surabaya City, with a correlation of 55%. The R-Square value of 0.733 or 73.3% means that changes in the positive consumer engagement variable can affect the buying interest variable by up to 73.3%. Therefore, it can be concluded that positive consumer engagement has a positive and significant effect on buying interest in BULOG rice in Surabaya City, with a correlation of 73.3%. R-Square value of 0.733 or 73.3% means that changes in the brand trust variable can affect the buying interest variable by up to 73.3%. Therefore, it can be concluded that brand trust has a positive and significant effect on buying interest in BULOG rice in Surabaya City, with a correlation of 73.3%